IMPLEMENTATION OF EFFECTIVE HR TOOLS INCREASING THE COMPETITIVENESS OF STAFF AS A WAREHOUSE TECHNOLOGY OF PROFESSIONAL DEVELOPMENT OF THE ENTERPRISE - VEDERNIKOV, Mykhailo; BAZALIYSKA, Natalia; SHELEST, Ievgeniia (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The competitiveness of the personnel is a significant factor in the formation of the competitive advantages of the enterprise. In particular, due to the high qualification level of the staff, such competitive advantages in the functioning of the enterprise as effective implementation of innovations, improvement of product quality, achievement of high labor productivity are ensured. Increasing the efficiency of the operation of the enterprise depends on the management of the competitiveness of the personnel, for which certain measures should be proposed, among which the most relevant are the hr-tools for increasing and evaluating the competitiveness of the personnel as a component of the technologies of the professional development of the enterprise, which requires further research into certain issues.The purpose of the article is to introduce effective HR tools to increase the competitiveness of personnel as a component of the enterprise's professional development technologies aimed at preserving and developing human potential, namely: ensuring effective employment; growth of wages and incomes; increasing the level of social security and social protection of employees; attraction of investments in continuous professional training at work; encouraging high motivation to work, creative realization of employees; striving for competitive advantages in work and continuous educational and professional development.The article examines the implementation of effective HR tools for increasing the competitiveness of personnel. The tools for increasing the competitiveness of personnel as a component of the enterprise's professional development technologies are summarized and systematized. The essential characteristics and value of the competitiveness of the enterprise's personnel as a component of the technologies of the enterprise's professional development are determined. HR tools for increasing the competitiveness of the company's personnel are given. The importance of the qualities of assessing the competitiveness of the company's personnel was determined. A personnel incentive system was built based on the results of increasing the competitiveness of the company's personnel. The results of the calculation of the integral indicator of the level of competitiveness of the management personnel of the enterprise are presented. Recommendations regarding gradations of results are substantiated by assessing the competitiveness of personnel as a component of the enterprise's professional development technologies.Therefore, the level of competitiveness and attractiveness of the business, its ability to survive in the competition and function effectively in the market with a certain level of guarantee of profitability directly depends on the level of competitiveness of the personnel.
Keywords: personnel competitiveness; hr-tools; personnel management; professional development of the enterprise; assessment of personnel competitiveness; enterprise